Infected pericardial effusion caused by Prevotella intermedia: a rare diagnosis - Xu, Wan; Han, Dan; Chen, Tianyang; Wang, Qian (Frontiers in Cellular and Infection Microbiology, 2025)
Prevotella intermedia is a Gram-negative bacterium that thrives in anaerobic environments. It presents challenges in detection through routine laboratory assays, and hitherto, there has been no documented instance of detecting this bacterium in pericardial effusion in China. Metagenomic Next-Generation Sequencing (mNGS) can boost the detection rate of this pathogen and furnish early guidance for clinical management.